The Introduction of Local Government in Mtubatuba: A Threat to the Local Traditional Authorities? - Nyathi, Patrick A. (CV. AFDIFAL MAJU BERKAH, 2024)
The events leading to the 1994 general elections marked a major turning point in the history of South Africa. The new dispensation saw the introduction of new legislation that would see traditional leaders ‘losing’ their powers to the newly established local government structures. The government’s White Paper on Local Government 1998 offered a new vision of a post-apartheid society, embodied in the concept of developmental local government. As a result, territories previously controlled by the traditional leaders would be divided into municipalities, each governed by an elected municipal council. This paper uses a combination of archival sources such as newspapers, minutes of the committee meetings and other written documentary and oral sources drawn from in-depth interviews with local leaders, traditional leaders, and local people from the area. It argues that the incorporation of remote traditional areas under the jurisdiction of traditional leaders in the newly formed municipalities threatened the powers of traditional leaders and complicated the jobs of newly elected councillors, as they were expected to go through izinduna for any project to be successfully launched. This was the case mainly in instances where a local traditional leader and a councillor belong to different political parties.